Pengaruh Rehabilitasi Berbantuan Robot terhadap Pemulihan Fungsional Setelah Total Hip Arthroplasty: Literature Review - Wijayanti, Dian Rahayu; Nabila, Kholida; Putri, Nadzifa Salsabila Haris; Azra, Nur Afrina; Olivia, Septina; Rahman, Farid (Jurnal Fisioterapi Terapan Indonesia, 2026)
Total Hip Arthroplasty (THA) remains a gold standard for restoring joint function in patients with severe hip osteoarthritis, yet achieving optimal functional recovery post-surgery remains a challenge. Robot-assisted rehabilitation (RAR) has emerged as a novel physiotherapy modality offering structured, repetitive, and sensor-driven training that may enhance recovery trajectories. Objective: This literature review aims to identify and synthesise current evidence on the effectiveness of RAR in improving functional outcomes after THA, focusing on gait performance, muscle strength, balance, and quality of life. Methods: A comprehensive search of PubMed, PEDro, ScienceDirect and Google Scholar was conducted for peer-reviewed articles published between 2015 and 2025. Studies included those evaluating robotic modalities in THA rehabilitation. Data extraction and narrative synthesis were guided by the PICO framework. Results: Eight studies met inclusion criteria. Robotic systems such as Hybrid Assistive Limb (HAL), Honda Walking Assist (HWA), Luna-EMG and Hunova demonstrated improvements in gait speed, stride length, lower limb strength, balance control and patient-reported functional scores compared with conventional therapy. Evidence supports enhanced neuromuscular coordination through individualized robot-based training. Conclusion: Robot-assisted rehabilitation appears to be a promising modality to support functional recovery after THA. Nevertheless, further large-scale studies with long-term follow-up are needed to confirm sustained benefits and cost-effectiveness for routine clinical practice.